Organic Electrochemical Transistors as Versatile Analytical Potentiometric Sensors - Gualandi, Isacco; Tessarolo, Marta; Mariani, Federica; Tonelli, Domenica; Fraboni, Beatrice; Scavetta, Erika (Frontiers in Bioengineering and Biotechnology, 2019)
Potentiometric transduction is an important tool of analytical chemistry to record chemical signals, but some constraints in the miniaturization and low-cost fabrication of the reference electrode are a bottleneck in the realization of more-advanced devices such as wearable and lab-on-a-chip sensors. Here, an organic electrochemical transistor (OECT) has been designed with an alternative architecture that allows to record the potentiometric signals of gate electrodes, which have been chemically modified to obtain Ag/AgnX interfaces (X = Cl−, Br−, I−, and S2−), without the use of a reference electrode. When the OECT is immersed in a sample solution, it reaches an equilibrium state, because PEDOT:PSS exchanges charges with the electrolyte until its Fermi level is aligned to the one of Ag/AgnX. The latter is controlled by Xn− concentration in the solution. As a consequence, in this spontaneous process, the conductivity of PEDOT:PSS changes with the electrochemical potential of the modified gate electrode without any external bias. The sensor works by applying only a fixed drain current or drain voltage and thus the OECT sensor operates with just two terminals. It is also demonstrated that, in this configuration, gate potential values extracted from the drain current are in good agreement with the ones measured with respect to a reference electrode being perfectly correlated (linear slope equal to 1.00 ± 0.03). In the case of the sulfide anion, the OECT performance overcomes the limit represented by the Nernst equation, with a sensitivity of 0.52 V decade−1. The presented results suggest that OECTs could be a viable option to fabricate advanced sensors based on potentiometric transduction.